2020
DOI: 10.1177/0300060520926036
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the relationship among alcohol, smoking, and Helicobacter pylori infection in asymptomatic individuals

Abstract: Objective We aimed to investigate the relationship of Helicobacter pylori infection with alcohol and smoking. Methods We conducted a cross-sectional study among participants who underwent health check-ups for H. pylori infection between January 2013 and March 2017. We subsequently investigated the relationship of H. pylori infection with alcohol and smoking. Results A total of 7169 participants were enrolled in this study. The overall prevalence of H. pylori infection was 55.2%. Participants with H. pylori inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“… 16 A recent study reported that the total prevalence of H. pylori infection among asymptomatic individuals was 55.2% in Wenzhou, China. 17 In our study, the prevalence of H. pylori infection was 35.0%, which is lower than the previously reported rate of 60% in the rural areas of China. 18 , 19 Considering that China is one of the most rapidly developing countries and that the socioeconomic status of residents has been improving significantly over recent decades, especially in the Shenzhen area where socioeconomic status and income levels are high, a declining trend in the prevalence of H. pylori infection may be occurring.…”
Section: Discussioncontrasting
confidence: 82%
“… 16 A recent study reported that the total prevalence of H. pylori infection among asymptomatic individuals was 55.2% in Wenzhou, China. 17 In our study, the prevalence of H. pylori infection was 35.0%, which is lower than the previously reported rate of 60% in the rural areas of China. 18 , 19 Considering that China is one of the most rapidly developing countries and that the socioeconomic status of residents has been improving significantly over recent decades, especially in the Shenzhen area where socioeconomic status and income levels are high, a declining trend in the prevalence of H. pylori infection may be occurring.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, age, occupation, the type of drinking water used, consumption of fruits, vegetables, or fried food are also independent risk factors for H. pylori infection [14][15][16]. Smoking and alcohol consumption were also found to be independently positively associated factors [17]. Many of these risk factors are preventable with adequate knowledge and appropriate practice.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the association of smoking and alcohol use on H. pylori prevalence are conflicting. Wu et al found that smoking and alcohol consumption were risk factors for H. pylori infection among adult males but were protective factors for females 40 . Murray et al reported that smoking is positively associated with H. pylori infection but not alcohol consumption 31 .…”
Section: Discussionmentioning
confidence: 99%